2014
DOI: 10.1371/journal.pone.0087881
|View full text |Cite
|
Sign up to set email alerts
|

Controlled versus Automatic Processes: Which Is Dominant to Safety? The Moderating Effect of Inhibitory Control

Abstract: This study explores the precursors of employees' safety behaviors based on a dual-process model, which suggests that human behaviors are determined by both controlled and automatic cognitive processes. Employees' responses to a self-reported survey on safety attitudes capture their controlled cognitive process, while the automatic association concerning safety measured by an Implicit Association Test (IAT) reflects employees' automatic cognitive processes about safety. In addition, this study investigates the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 61 publications
(98 reference statements)
2
18
0
Order By: Relevance
“…For example, in one prior study, inhibitory control moderated the effect of implicit attitudes on food intake, such that positive implicit attitudes were only associated with increased food intake among those low in inhibitory control capacity (Haynes, Kemps, & Moffitt, 2015). Another research group examining the dual-process model in the context of employee safety found that individuals’ automatic bias towards risk predicted failure to comply with safety regulations in the workplace, but only for those with poor inhibitory control (Xu, Li, Ding, & Lu, 2014). Also, in a study examining implicit attitudes towards alcohol and self-reported drinking behavior, the association between implicit attitudes and behavior was moderated by activity in the lateral prefrontal cortex, a neural correlate of inhibitory control (Friese, Gianotti, & Knoch, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in one prior study, inhibitory control moderated the effect of implicit attitudes on food intake, such that positive implicit attitudes were only associated with increased food intake among those low in inhibitory control capacity (Haynes, Kemps, & Moffitt, 2015). Another research group examining the dual-process model in the context of employee safety found that individuals’ automatic bias towards risk predicted failure to comply with safety regulations in the workplace, but only for those with poor inhibitory control (Xu, Li, Ding, & Lu, 2014). Also, in a study examining implicit attitudes towards alcohol and self-reported drinking behavior, the association between implicit attitudes and behavior was moderated by activity in the lateral prefrontal cortex, a neural correlate of inhibitory control (Friese, Gianotti, & Knoch, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…While the RIM has proven to be useful to predict behaviors relating to employee safety [11] , voting [12] and health (see [8] , [13] for reviews), only two studies have assessed impulsive processes to prospectively predict PA behaviors [10] , [14] . The Conroy et al study revealed that impulsive processes towards PA accounted for variability in walking behavior over a 7-day pedometer assessed monitoring period above and beyond reflective processes (e.g., behavioral intentions).…”
Section: Introductionmentioning
confidence: 99%
“…Then, the Stroop interference score was calculated by subtracting median incongruent response time from median congruent response time. Thus, higher Stroop interference scores indicated higher self-control [ 9 ]. In addition to the Stroop interference score, which is a behavioral measure of state self-control, we also assessed self-reported trait self-control with the Tangney Self-Control Scale (SCS; [ 13 ]).…”
Section: Methodsmentioning
confidence: 99%
“…We examined these interactions because it has been demonstrated that boundary conditions, such as self-control, moderate the influence of reflections and impulses on behavior [ 8 ]. For example, Xu, Li, Ding, and Lu (2014) revealed that nuclear power plant workers with high self-control had their safety behaviors driven by reflections, presumably because they were able to inhibit their impulse in order to follow through on their reflections about safety [ 9 ]. Conversely, workers with low self-control had their safety behaviors guided by impulses, presumably because they were unable to inhibit their impulse about safety.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation